Adult education. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows a Japanese teacher instructing a group of adults at Tanforan Assembly Center in San Bruno, California.